2011
DOI: 10.5658/wood.2011.39.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Charcoal from Major Korean Wood Species and Wood-based Materials (II)

Abstract: We analyzed the basic characteristics and adsorption property of carbonized materials from thinning byproducts of major Korean wood species for evaluating as charcoal making raw material. Yield of charcoal was decreased with increasing the carbonization temperature for all wood species. Refining degrees was 9.0 at 400°C, 3.3∼5.0 at 600°C and 0 at 800°C, and was no-281-1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…Shin and Kim (2013) reported that the volatile matter ranged from 5.67% to 7.65%. In contrast, Lee and Kim (2011) reported that volatile matter ranged from 8.6% to 11.8% at 800 °C, which is slightly higher than the values reported in the current study.…”
Section: Comparison Of Physical Characteristics and Proximate Analysis Of Charcoal Produced Over One Year From Thermal Therapy Kilnscontrasting
confidence: 99%
See 1 more Smart Citation
“…Shin and Kim (2013) reported that the volatile matter ranged from 5.67% to 7.65%. In contrast, Lee and Kim (2011) reported that volatile matter ranged from 8.6% to 11.8% at 800 °C, which is slightly higher than the values reported in the current study.…”
Section: Comparison Of Physical Characteristics and Proximate Analysis Of Charcoal Produced Over One Year From Thermal Therapy Kilnscontrasting
confidence: 99%
“…The fixed carbon of charcoal from the thermal therapy kilns ranged from 84% to 90% over one year. Lee and Kim (2011) reported that the fixed carbon was 79.3% from Q. acutissima and 80.2% from Q. serrata. Shin and Kim (2013) found that the fixed carbon of charcoal from Q. phillyraeoides ranged from 86.31% to 85.97%.…”
Section: Comparison Of Physical Characteristics and Proximate Analysis Of Charcoal Produced Over One Year From Thermal Therapy Kilnsmentioning
confidence: 99%
“…When this process is performed at high temperature, it produces solid (charcoal), liquid (water and organics), gas (CO, CO 2 , CH 4 , H 2 ), carbonaceous aerosol pollutants (Organic Carbon or OC, Elemental Carbon or EC, etc. ) and particular matters (PM2.5 and PM10) and those compositions are strongly dependent on the nature of feedstock, the process conditions, kiln types, carbonization temperature and the adopted technologies (FAO, 1987;Madani et al, 1992;Jo et al 2005;Lee and Kim, 2010 a;Lee and Kim, 2011;de Carvalho et al, 2013;Chidumayo and Gumbo, 2013;Jeong et al, 2016;Magnone et al, 2016;Yang et al, 2017;Kang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Lee and Kim (2011), higher specific surface area had higher moisture absorption capacity. In general, black (soft) charcoal which made at lower temperature (below 600℃) has 0.1-13.7 m 2 /g of specific surface area, and white (hard) charcoal which made at higher temperature (above 800℃) has 53.2-372.6 m 2 /g of specific surface area .…”
Section: Performance Of Moisture Absorption and Desorptionmentioning
confidence: 99%